The Many Faces of Health, Competence and Well-Being in Old Age Integrating Epidemiological, Psychological and Social Perspectives - Wahl, Hans-Werner.; Brenner, Hermann; Mollenkopf, Heidrun; Rothenbacher, Dietrich; Rott, Christoph; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The main aim of the book is to provide an interdisciplinary treatment of a set of key issues of current ageing research, i.e., health, competence, and well-being. These key issues are addressed based on three converging research streams: social-ecological research, which assumes that major processes and outcomes of ageing such as day-to-day competence are shaped by social and physical-spatial environments; geropsychology research, which is driven by a life-span developmental conception of ageing; and epidemiology, which offers most fundamental disease, function and prevention-related data. Each of the three major research directions are outlined by a short introduction, followed by three chapters treating in an empirical manner most recent key research questions. All chapters are then also discussed by renowned ageing experts. This volume links ageing research with policy considerations and implications and establishes a link between European research and the knowledge base of the international scientific community concerned with ageing. This book will be of great interest to scholars and graduate students in ageing research, in the social and behavioural field as well as in epidemiology, geriatrics, geropsychiatry, demography, and biogerontology.
FOCUSING ON SOCIAL-ECOLOGICAL RESEARCH-CONTRIBUTIONS TO HEALTH, COMPETENCE, AND WELL-BEING IN OLD AGE -- FOCUSING ON SOCIAL-ECOLOGICAL RESEARCH-CONTRIBUTIONS TO HEALTH, COMPETENCE, AND WELL-BEING IN OLD AGE -- INTRODUCTION: THE PERSON-ENVIRONMENT PERSPECTIVE IN AGEING RESEARCH -- THE ROLE OF THE HOME ENVIRONMENT IN MIDDLE AND LATE ADULTHOOD -- COMMENTARY: A HOUSE IS NOT A HOME: BUT CAN IT BECOME ONE? -- OUTDOOR MOBILITY IN LATE LIFE: PERSONS, ENVIRONMENTS AND SOCIETY -- COMMENTARY: MOBILITY-A KEY TO UNDERSTANDING AND IMPROVING TRANSPORTATION SERVICES FOR SENIORS AND OTHERS -- AGE-RELATED LOSS IN VISION: A CASE TO LEARN ABOUT AGEING IN CONTEXT -- COMMENTARY: AGE-RELATED LOSS IN VISION: A CASE TO LEARN ABOUT AGING IN CONTEXT -- FOCUSING ON PSYCHOLOGICAL RESEARCH-CONTRIBUTIONS TO HEALTH, COMPETENCE, AND WELL-BEING IN OLD AGE -- FOCUSING ON PSYCHOLOGICAL RESEARCH-CONTRIBUTIONS TO HEALTH, COMPETENCE, AND WELL-BEING IN OLD AGE -- INTRODUCTION: DEVELOPMENTAL PERSPECTIVES IN THE SECOND HALF OF LIFE -- THE INFLUENCE OF MARITAL SUPPORT ON MARITAL SATISFACTION: ARE THERE AGE AND GENDER DIFFERENCES? -- COMMENTARY: CHANGED GENDER ROLES AND THEIR IMPACT ON MARITAL SUPPORT AND SATISFACTION -- STRESSFUL LIFE EVENTS, PROTECTIVE FACTORS AND DEPRESSIVE DISORDERS IN MIDDLE ADULTHOOD -- COMMENTARY: STRESSFUL LIFE EVENTS AND DEPRESSIVE DISORDERS: THE PARADIGM SHIFT -- PREDICTORS OF WELL-BEING IN VERY OLD AGE -- COMMENTARY: WELL-BEING IN VERY OLD AGE: OLD AND NEW ISSUES -- FOCUSING ON EPIDEMIOLOGICAL RESEARCH-CONTRIBUTION TO HEALTH, COMPETENCE, AND WELL-BEING -- FOCUSING ON EPIDEMIOLOGICAL RESEARCH-CONTRIBUTION TO HEALTH, COMPETENCE, AND WELL-BEING -- INTRODUCTION: EPIDEMIOLOGICAL PERSPECTIVES IN AGEING RESEARCH -- CANCER AMONG OLDER ADULTS: INCIDENCE, PROGNOSIS AND NEW AVENUES OF PREVENTION -- COMMENTARY: CANCER IN THE ELDERLY: PREVENTION AND BETTER CARE NEEDED -- CARDIOVASCULAR DISEASES AMONG OLDER ADULTS: INCIDENCE, PROGNOSIS AND NEW AVENUES FOR PREVENTION -- COMMENTARY: CARDIOVASCULAR DISEASES AMONG OLDER ADULTS: INCIDENCE, PROGNOSIS AND NEW AVENUES FOR PREVENTION -- MEDICAL CARE FOR NURSING HOME RESIDENTS: NATIONAL PERSPECTIVES IN INTERNATIONAL CONTEXT -- COMMENTARY: MEDICAL CARE FOR NURSING HOME RESIDENTS: NATIONAL PERSPECTIVES IN INTERNATIONAL CONTEXT -- SYNERGIES BETWEEN SOCIAL-ECOLOGICAL, PSYCHOLOGICAL AND EPIDEMIOLOGICAL RESEARCH -- SYNERGIES BETWEEN SOCIAL-ECOLOGICAL, PSYCHOLOGICAL AND EPIDEMIOLOGICAL RESEARCH -- THE IMPACT OF INTERNAL AND EXTERNAL RESOURCES ON HEALTH, COMPETENCE AND WELL-BEING: LONGITUDINAL FINDINGS FROM THE ILSE -- DETERMINANTS, PROGNOSTIC RELEVANCE AND DEVELOPMENT OF ANXIETY AND DEPRESSION IN PATIENTS WITH CORONARY HEART DISEASE: AN INTERDISCIPLINARY APPROACH WITHIN THE KAROLA STUDY -- COMMENTARY: INTERDISCIPLINARY LONGITUDINAL STUDIES OF AGEING -- APPLICATIONS AND SOCIAL POLICY IMPLICATIONS -- APPLICATIONS AND SOCIAL POLICY IMPLICATIONS -- AGEING EUROPE: CHALLENGES FOR POLICY AND RESEARCH -- ON THE RELEVANCE OF AGEING RESEARCH FOR POLICY AND PRACTICE.
Keywords: GERIATRICS; QUALITY OF LIFE; SOCIAL SCIENCES; QUALITY OF LIFE -- RESEARCH; DEMOGRAPHY; DEVELOPMENTAL PSYCHOLOGY; SOCIAL SCIENCES, GENERAL; SOCIAL SCIENCES, GENERAL; DEMOGRAPHY; QUALITY OF LIFE RESEARCH; COMMUNITY & ENVIRONMENTAL PSYCHOLOGY; GERIATRICS/GERONTOLOGY.; DEVELOPMENTAL PSYCHOLOGY